The image of the horse in Tuvan riddles - Soyan, Aylanmaa M. (The New Research of Tuva, 2023)
The article presents an analysis of the image of the horse in Tuvan riddles. The study material consists of 94 riddles selected using the continuous sampling method from the book entitled “Tuvan Riddles” (“Tyva Tyvyzyktar”, compiled by Georgy N. Kurbatskii), which was published in 2018. It is shown that in Tuvan riddles the age and gender terms that are used to name horses (askyr ‘stallion’, aъt ‘steed, horse, gelding’, bogba ‘yearling’, be ‘mare’, kulun ‘foal’, chavaa ‘yearling’), their coat colors and types of gait serve to create original images of other animals, birds, insects, natural phenomena, elements of water and fire, household items, the traditional dwelling of nomads (yurts), technical devices, means of transportation. The author also considers the interrelation between riddles and myths, which is reflected in the texts of Tuvan riddles. The types of tropes often found in Tuvan riddles are noted: metaphors, metaphorical epithets and synecdoche. In addition to traditional riddles, the Tuvans have other riddles that were created in Soviet times. They comprise an airplane, a bicycle, a tractor, a cart that are depicted using the image of a horse. These riddles should be correctly considered as pseudo-paroemias.